Brain Tissue Oxygen Monitoring to Assess Reperfusion after Intra-Arterial Treatment of Aneurysmal Subarachnoid Hemorrhage−Induced Cerebral Vasospasm: A Retrospective Study - Deshaies, E.M.; Jacobsen, W.; Singla, A.; Li, F.; Gorji, R. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Cerebral vasospasm resistant to medical management frequently requires intra-arterial spasmolysis. Angiographic resolution of vasospasm does not provide physiologic data on the adequacy of reperfusion. We recorded pre- and postspasmolysis PbO2 data in the endovascular suite to determine whether this physiologic parameter could be used to determine when successful reperfusion was established. MATERIALS AND METHODS: Eight patients with 10 Licox monitors and cerebral vasospasm underwent intra-arterial spasmolysis. Pre- and postspasmolytic PbO2 was recorded for comparison. Other physiologic parameters, such as CPP, ICP, SaO2, and Fio2, were also recorded. RESULTS: Mean prespasmolysis PbO2 recordings were 35.2 and 27.3 for the mild-to-moderate and moderate-to-severe vasospasm group, respectively. Mean postspasmolysis PbO2 increased to 40.3 and 38.4, respectively, which was statistically significant (P < .05) for both groups. In 100% of instances in the moderate-to-severe group and 83% of instances in mild-to-moderate group, the mean PbO2 increased after spasmolysis and correlated with improvement in angiographic vasospasm. Other physiologic parameters, such as CPP, ICP, SaO2, and Fio2, did not show any statistically significant difference before and after spasmolysis. CONCLUSIONS: PbO2 monitoring provides the interventionalist with an objective physiologic parameter to determine adequate spasmolysis. Further investigation is needed to establish target PbO2 rates indicative of adequate reperfusion, which can be used in the endovascular suite. ACAanterior cerebral arteryCPPcerebral perfusion pressureCVcerebral vasospasmFio2fraction of inspired oxygenICPintracranial pressureICUintensive care unitPbO2partial brain tissue oxygen tensionSaO2arterial oxygen saturationSEstandard error